Fotografi Pertunjukan: Fenomenena Tubuh dari Panggung menjadi Rupa - RY. ADAM PANJI PURNAMA (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2009)
Performace Photography: The Body Phenomenon from Stage to Physical. Performance photographyhas tried its best to capture the phenomena on stage. These two art mainstreams are completely different both fromthe subject and the objects. Performing art utilizes eyes and noses as the guidance to the feeling and meaningfulbody movements. Meanwhile, photography only utilizes eyes due to the still images it uses. Body in the performanceis the amalgamation of physical body and spiritual body. The detachment from a daily life to act as others accordingto the performance demand makes a performance meaningful and atmospheric for the audience.